Factors associated with participation in a proton therapy clinical trial: a cross-sectional survey of Danish patients with head and neck cancer - Anne Wilhøft Kristensen; Kenneth Jensen; Annesofie L. Jensen; Susanne O. Dalton; Jesper Eriksen; Jeppe Friborg; Cai Grau (Acta Oncologica, 2025)
Background and purpose: Participation in proton therapy (PT) trials may be affected by structural, clinical, and individual factors, potentially excluding certain patient groups. Such disparities can lead to unequal access to potential research benefits and may limit the generalisability of trial findings. This study aimed to identify factors associated with participation in a Danish randomised controlled trial (RCT) comparing proton versus photon radiotherapy for head and neck cancer.